2023
DOI: 10.3390/nu15071751
|View full text |Cite
|
Sign up to set email alerts
|

Aspalathus linearis (Rooibos) Targets Adipocytes and Obesity-Associated Inflammation

Abstract: Excess weight and obesity are the fifth leading cause of death globally, and sustained efforts from health professionals and researchers are required to mitigate this pandemic-scale problem. Polyphenols and flavonoids found in Aspalathus linearis—a plant widely consumed as Rooibos tea—are increasingly being investigated for their positive effects on various health issues including inflammation. The aim of our study was to examine the effect of Rooibos extract on obesity and the associated low-grade chronic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Recently, research results on food components or phytochemicals that ameliorate obesity-associated inflammation have emerged. Basil seed [36] and rooibos [37] inhibited adipogenesis and pro-inflammatory cytokine expression in vitro, and anthocyanins attenuated obesity and associated inflammation by modulating the secretion of inflammatory adipokines in several animal and clinical studies [38]. Here, we observed that HFD induced the enlargement of adipocytes and significantly increased the mRNA levels of proinflammatory adipokines, such as TNF-α, MCP-1, PAI-1, leptin, and resistin in the WAT.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, research results on food components or phytochemicals that ameliorate obesity-associated inflammation have emerged. Basil seed [36] and rooibos [37] inhibited adipogenesis and pro-inflammatory cytokine expression in vitro, and anthocyanins attenuated obesity and associated inflammation by modulating the secretion of inflammatory adipokines in several animal and clinical studies [38]. Here, we observed that HFD induced the enlargement of adipocytes and significantly increased the mRNA levels of proinflammatory adipokines, such as TNF-α, MCP-1, PAI-1, leptin, and resistin in the WAT.…”
Section: Discussionmentioning
confidence: 54%
“…The antioxidant capacity of rooibos also links closely to an anti-inflammatory outcome. In this context, data from in vitro models of inflammation associate rooibos administration with improved tight junction protein expression and interaction status to maintain endothelial cellular structure and barrier integrity ( Ku et al, 2015 ; Lee and Bae, 2015 ; Pretorius and Smith, 2022 ), modulation of PGE2 synthesis ( Hedbrant et al, 2022 ), inhibition of basophil activation ( Pedretti and Peter, 2020 ) and an inhibitory effect on concentrations of pro-inflammatory mediators–such as IL-1α, IL-6, IL-8, VCAM-1 and ATF4 gene expression ( Lawal et al, 2019b ), as well as IFN-γ, IL-12, IL-2, IL-17a, TNF-α, IL-8, IL-6, IL-1β and CXCL10 ( Nehme et al, 2023 )–and increased anti-inflammatory cytokine, IL-10 ( Ichiyama et al, 2007 ). In addition, the flavonoid actives aspalathin and nothofagin were reported to prevent the expression of cell adhesion molecules and transendothelial migration of neutrophils in LPS- and high glucose-exposed cells ( Ku et al, 2015 ; Lee and Bae, 2015 ), while other rooibos constituents quercetin, luteolin and chrysoeriol reportedly inhibited antigen- and calcium ionophore-stimulated degranulation in basophils ( Morishita et al, 2019 ).…”
Section: Rooibos: Doomed To Fail or On The Road To Success?mentioning
confidence: 99%